Adapting fluorescence resonance energy transfer with quantum dot donors for solid-phase hybridization assays in microtiter plate format - Petryayeva, Eleonora (Langmuir : the ACS journal of surfaces and colloids, 2013)
Methods have been developed for the solid-phase detection of nucleic acids using mixed films of quantum dots (QDs) and oligonucleotide probes in microtiter plates. Polystyrene microwells were functionalized with multidentate imidazole ligands to immobilize QDs. Oligonucleotide hybridization was transduced using QDs as donors in fluorescence resonance energy transfer (FRET). One detection channel paired green-emitting QD donors with Cy3 acceptors and served as an internal standard. A second detection channel paired red-emitting QDs with Alexa Fluor 647 acceptors and served as the primary detection channel. A selective assay for multiple targets was demonstrated using a 96-well plate format, which combined the advantages of two-plex QD-FRET with the high-throughput capability and convenience of microtiter plates. The assay had excellent resistance to the nonspecific adsorption of DNA and discriminated between fully complementary and single base-pair mismatched sequences with a contrast ratio >2. Under optimal conditions for a single color (green QD) assay format, the limit of detection (LOD) was 4 nM, and the dynamic range was from 20 to 300 nM. In a two-color assay, the detection channel (red QD) exhibited linear response between 4 and 100 nM and a LOD of 4 nM